α-(Phenylthio)cyclopropylation of carbonyl compounds: Preparation of α-cyclopropyl ketones - Manat Pohmakotr (2018)
α-Chloro-α-(phenylthio)cyclopropane and α-acetoxy-α-(phenylthio)cyclopropane were found to react with the silyl enol ethers of some ketones in the presence of Lewis acid in dichloromethane to provide α-(phenylthio)cyclopropyl ketones, which were subjected to reduction with Ra-Ni to give the corresponding α-cyclopropyl ketones.